ChemInform Abstract: Open Source Drug Discovery with Bioclipse. Issue 31 (11th July 2013) - Spjuth, Ola; Carlsson, Lars; Alvarsson, Jonathan; Georgiev, Valentin; Willighagen, Egon; Eklund, Martin
Abstract Review: 67 refs.